SEC/MALLS measurement of the branched structure of methyl methacrylate + ethylene glycol dimethacrylate copolymers synthesized by atom transfer radical polymerization - Trigo, Ivone (2008)
In the last few years, atom transfer radical polymerization (ATRP) of acrylate and methacrylate monomers in the presence of a small amount of cross-linker has been investigated in order to produce branched polymers and gels with applications in microelectronics, coatings industries or biomedicine (Wang and Zhu, 2005; Gao et al., 2007). In this context, it is being explored the production by ATRP of branched/crosslinked polymers with a lower degree of heterogeneity than that obtained by conventional free radical polymerization (FRP). This work reports an experimental study on the ATRP of methyl methacrylate (MMA) + ethylene glycol dimethacrylate (EGDMA) initiated by MBPA (methyl -bromophenylacetate) and mediated by copper bromide (CuBr) ligated with HMTETA (1,1,4,7,10,10- hexamethyltriethylenetetramine). The synthesized copolymers were analyzed by size exclusion chromatography (SEC) with simultaneous detection of refractive index (RI) and multi-angle laser light scattering (MALLS) signals. Important details of the molecular architecture of these materials can therefore be measured, namely absolute molecular weights and z-average radius of gyration. Different experimental runs were performed in order to investigate the influence of the operating conditions (e.g. temperature and initial molar ratios MMA/EGDMA/MBPA/CuBr/HMTETA) on the structure of the products.